The algorithms of adjuvant therapy in gliomas and their effect on survival - Straube, Christoph; Schmidt-Graf, Friederike; Wiestler, Benedikt; Zimmer, Claus; Meyer, Bernhard; Combs, Stephanie E. (Journal of Neurosurgical Sciences, 2019)
The treatment of gliomas became more sophisticated during the last decades. As by now, adjuvant treatment after maximum safe resection is considered an important and effective treatment strategy in most gliomas, yet the decision is based on several factors. This review summarizes the available evidence for the current adjuvant treatment algorithms with a focus on the impact on the survival of glioma patients. The review is based on the current guidelines, but it also includes new insights which have not yet been included into the official guidelines.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adjuvant radiotherapy; Glioblastoma; Glioma; Oligodendroglioma